2001
DOI: 10.5194/hess-5-433-2001
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality, water quality trends and biological responses in four streams in the Cairngorm Mountains, Scotland

Abstract: The chemical composition and invertebrate communities found in four streams in the Cairngorms, Scotland, were monitored between [1985][1986][1987][1988][1989][1990][1991][1992][1993][1994][1995][1996][1997]. Stream waters were mildly acidic (mean pH ca. 6.5), with low alkalinity (mean acid neutralising capacity varying from 35-117 meq l -1 ) and low ionic strength. Subtle differences in the chemistry of each stream were reflected in their invertebrate faunas. Strong seasonality in water chemistry occurred, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…Therefore, the results of the CCA reflected the lack of flow regime influence on the benthic communities, as evidenced by the eigenvalues. The eigenvalues of the four axes (axis1: 0.165, axis 2: 0.118, axis 3: 0.095, axis 4: 0.056) were lower than those reported by Tang et al (2002) and Leland and Porter (2000), suggesting that variables other than those measured (e.g., alkalinity, Na, Mg, K, SO 4 , and HCO 3 content) may have an important influence on benthic-algal community characteristics (Soulsby et al 2001).…”
Section: Comparison Among Different Groupsmentioning
confidence: 41%
“…Therefore, the results of the CCA reflected the lack of flow regime influence on the benthic communities, as evidenced by the eigenvalues. The eigenvalues of the four axes (axis1: 0.165, axis 2: 0.118, axis 3: 0.095, axis 4: 0.056) were lower than those reported by Tang et al (2002) and Leland and Porter (2000), suggesting that variables other than those measured (e.g., alkalinity, Na, Mg, K, SO 4 , and HCO 3 content) may have an important influence on benthic-algal community characteristics (Soulsby et al 2001).…”
Section: Comparison Among Different Groupsmentioning
confidence: 41%
“…2) when surface warming supports Si and NO 3 depletion by phytoplankton and uptake of Si from soil solutions by vegetation (Farmer et al, 2005;Soulsby et al, 2001). This seasonal variation occurs only in this lake and is superimposed on the long-term increase of Si concentrations observed for both the July and October sampling (Fig.…”
Section: Long-term Trends In Si Concentrationsmentioning
confidence: 92%
“…Si may inhibit Al-induced reduction of bioavailable phosphorus by binding Al preferentially. Short-term variability of Si concentrations in streams relates to hydrology (Johnson et al, 1969), season (Norton et al, 1999;Gèrard et al, 2002;Soulsby et al, 2001) and diatom utilisation (Clarke, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…He attributed the differences in community composition (and hence BI values) to the influences of temperature seasonality on invertebrate life histories, but noted that "stream temperature does not appear to affect the BI, except for its influence on seasonal differences" (Hilsenhoff 1988). Soulsby et al (2001) found that invertebrate communities change seasonally largely as a result of variation in their species life cycles. However, we expected that biotic index seasonality in New Zealand would not be strongly linked to the presence, absence, or relative abundances of invertebrates owing to their life histories.…”
Section: Species Traitsmentioning
confidence: 99%